Diagnostic and Prognostic Potential of Circulating and Tissue BATF2 in Nasopharyngeal Carcinoma - Cui, Zhaolei; Lin, Yingying; Hu, Dan; Wu, Jing; Peng, Wei; Chen, Yan (Frontiers in Molecular Biosciences, 2021)
BACKGROUND: Current biomarkers for nasopharyngeal carcinoma (NPC) are less effective for early diagnosis and prognosis. The basic leucine zipper ATF-like transcription factor 2 (BATF2) gene has been shown to have a tight association with the pathogenesis of various malignancies but received scant attention in NPC research. We aimed to assess the performances of circulating and tissue BATF2 in the diagnosis and prognosis of NPC. MATERIALS AND METHODS: Immunohistochemistry (IHC) microarrays were performed to quantitate the BATF2 protein expression in NPC tissues. The relationships of BATF2 protein expression with clinicopathological characteristics and NPC prognosis were assessed. BATF2 mRNA expressions in serum and serum-derived exosomes were determined using quantitative reverse transcription-polymerase chain reaction (qRT-PCR) assay. RESULTS: The IHC microarrays revealed a predominant nuclear expression of BATF2 in NPC cells. The Kaplan-Meier survival analysis showed that BATF2-positive NPC patients enjoyed longer overall survival than BATF2-negative patients. NPC patients with serum and exosomal BATF2 mRNA expressions made up 51.47% and 48.52% of all patients, respectively. The AUCs of serum and exosomal BATF2 mRNA expressions in discriminating NPC from healthy controls were 0.9409 and 0.8983. Patients who had received radiochemotherapy exhibited higher serum and exosomal BATF2 mRNA expressions versus the levels at baseline as well as those detected in recurrent patients. CONCLUSION: BATF2 is expressed cancerous tissues, serum, and serum-derived exosomes in NPC patients. Circulating and tissue BATF2 mRNA can serve as a multipurpose biomarker capable of the diagnosis, prognosis prediction, efficacy evaluation, and recurrence monitoring in NPC.